Integration of Internet of Things (IoT)-Based Technological Innovation and Product Branding in Strengthening the Student Entrepreneurship Ecosystem at the Unsulbar Farming Club - Kalsum, Ummu; Wahyuni, Wahyuni; Sahabuddin, Romansyah; Bado, Basri (Universitas Sulawesi Barat, 2025)
This study aims to analyze the integration of Internet of Things (IoT)-based technological innovations and product branding strategies in strengthening the student entrepreneurship ecosystem at the Farming Club, University of West Sulawesi (Unsulbar). The research employs a mixed-methods approach, combining quantitative and qualitative methods. The quantitative approach is used to measure the increase in productivity and income from harvests after implementing the IoT system, while the qualitative approach explores students’ perceptions and the impact of innovation implementation on entrepreneurial development. The results show that the implementation of an IoT-based automation system using an ESP32 microcontroller, ultrasonic sensors, and a digital monitoring application successfully increased watering efficiency by 40% and reduced water waste as well as labor requirements. Economically, the integration of IoT and product branding increased the income of the Unsulbar Farming Club by 57.4% per harvest cycle. The new packaging and logo design labeled “UFC Hydroponics Vegetables” with the slogan “Petani Milenial, Petani Keren” (Millennial Farmers, Cool Farmers) proved to enhance product appeal, strengthen brand image, and expand market reach. This study concludes that the combination of IoT technology implementation and product branding strategies plays a crucial role in strengthening the student entrepreneurship ecosystem. The integration not only contributes to higher productivity and income but also fosters innovative, creative, and competitive student character in the digital era